Asymmetric Decentralisation: Autonomous Power Sharing Between Jakarta and Ibu Kota Nusantara - Putri, Aulia Kartika; Purwaningsih, Titin (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze the concept of asymmetric decentralization and the implications of implementing asymmetric decentralization in the context of moving the national capital from Jakarta to Ibu Kota Nusantara. This study used a normative juridical method with a legislative approach and a conceptual approach. The results of the study show that asymmetric decentralization as applied in Indonesia can be seen in the efforts to relocate the national capital as regulated by Law Number 2 of 2024. The relocation of the national capital from Jakarta to Ibu Kota Nusantara leads to the concept of functional asymmetric decentralization, which emphasizes the division of power based on function and productivity rather than geographical boundaries. The relocation of the capital from Jakarta to Ibu Kota Nusantara has implications for governance, triggering various problems, including infrastructure and resource capacity imbalances, the emergence of social polarization and urban gentrification, and overlapping authorities and policies due to the absence of a legal framework that explicitly regulates coordination between Jakarta and Ibu Kota Nusantara.